East Indian Child, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2008)
Photograph of a little boy wearing a beaded necklace and a simple loincloth with his belongings securely tied with a string in his right hand.
Colour: Brown and White; Style: Portrait; Other: Bordered, Divided
Keywords: Postcards; East Indians--Trinidad and Tobago; Children--Trinidad and Tobago; Trinidad and Tobago